The theology of the apostles the development of New Testament theology - Schlatter, Adolf von, 1852-1938; Kostenberger, Andreas J. (Grand Rapids, MI Baker, 1998)
Includes bibliographical references and indexes.
Originially published : Die Theologie der Apostel : Stuttgart : Calwer Vereinbuchhandlung, 1922
Keywords: Apostles; Bible. N.T. -- history of contemporary events; Theology -- history -- early church, ca. 30-600.